2015
DOI: 10.1007/s00606-015-1226-x
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction biology and chloroplast inheritance in Bromeliaceae: a case study in Fosterella (Pitcairnioideae)

Abstract: We applied a series of intra-and interspecific in situ cross-pollination experiments under greenhouse conditions to evaluate the breeding systems in four Fosterella species (Pitcairnioideae s.str.; Bromeliaceae). Viable hybrids were produced between each pair of the investigated species, suggesting that reproduction barriers may be low also under natural conditions. Seed germination rates proved to be high in each crossing treatment, indicating a high viability of the artificial hybrids. Large numbers of seeds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…; Wagner et al . ; Neri et al . , ) studies have recognised that selfing rather than outcrossing rates hamper hybridization and introgression, and thus represent an important pre‐zygotic reproductive isolation barrier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Wagner et al . ; Neri et al . , ) studies have recognised that selfing rather than outcrossing rates hamper hybridization and introgression, and thus represent an important pre‐zygotic reproductive isolation barrier.…”
Section: Discussionmentioning
confidence: 99%
“…; Wagner et al . ) and natural hybridization has been recorded in some species (Gardner ; Luther ; Wendt et al . , ; Gonçalves & de Azevêdo‐Gonçalves ; Schulte et al .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the presence of plastid DNA haplotypes of both parental species in the hybrids (Fig. 4) suggests that hybridization is bidirectional between these two species, considering that the plastid genome in Bromeliaceae is maternally inherited (Wagner et al, 2015). Palma-Silva et al (2011) also observed that hybridization between Pitcairnia albiflos Herb.…”
Section: Evidence Of Hybridization Betweenmentioning
confidence: 95%
“…Observed and expected heterozygosity values ranged from zero to 1 and from 0.17 to 0.83, respectively. Significant deviations from HWE in terms of heterozygote deficiency were detected at three loci (Foc_01, Foc_05, Foc_12) in population NW09.005 and at one locus (Foc_18) in population NW09.034, which is possibly explained by the potential of Fosterella species to self-pollinate (Wagner et al, 2015). With one exception (Foc_04), all 13 loci were also polymorphic in F. micrantha (two to 11 alleles) and in F. villosula (two to six alleles) (Table 2).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Such high levels of similarity are surprising, given that F. micrantha is endemic to Central America, whereas the other two species reside in the Bolivian Andes. Controlled pollination experiments indicated that all three species are self-compatible but also form viable hybrids (Wagner et al, 2015). To investigate the genetic diversity and differentiation in this closely related species complex, we used Pacific Biosciences’ single-molecule real-time (SMRT) technology (Eid et al, 2009) to develop a set of genic microsatellite markers in F. christophii .…”
mentioning
confidence: 99%